DETERMINATION OF PARACETAMOL LEVELS USING THE UV-VIS SPECTROPHOTOMETRY METHOD - Abd Sukri S Manusu; Nabila Ramadhani; Eva Larassati; Baiq Husnul Hotimah Septiandi (Asian Journal of Analytical Chemistry, 2023)
Paracetamol is analgesic and antipyretic Which introduced on treatment on year 1950s. Paracetamol reduces pain by inhibiting the cyclooxygenase enzyme and preventing the production of prostaglandins in the central and peripheral nervous system. Ultraviolet-visible (UV -Vis) is a technique used to analyze substances containing components that absorb in the visible ultraviolet region. The advantages of the UV-Vis method are that the analysis technique is fast, the equipment is easy to use, uses less solvent and reagents, and is more cost effective. The operating principle of a UV-Vis (Ultra Violet-Visible) spectrophotometer is based on light absorption, where atoms and molecules interact with light. The aim of this research is to develop or validate a fast, accurate and efficient analytical method for determining the concentration of paracetamol in various drugs or medicines, thus supporting monitoring of the quality, safety and effectiveness of these products in a product. clinic s. The validation results of this method show that this method is good for detecting mefenamic acid in herbal medicine with a correlation coefficient (r) of 0.9478 and (r2 ) of 0.9736; limit of detection (LOD) 13.42679 ppm; limit of quantification (LOQ) 44.75595. The herbal medicine samples contained paracetamol on average 5,487 ppm.